2000
DOI: 10.1101/gad.14.4.403
|View full text |Cite
|
Sign up to set email alerts
|

The carboxyl terminus of vertebrate poly(A) polymerase interacts with U2AF 65 to couple 3′-end processing and splicing

Abstract: Although it has been established that the processing factors involved in pre-mRNA splicing and 3′-end formation can influence each other positively, the molecular basis of this coupling interaction was not known. Stimulation of pre-mRNA splicing by an adjacentcis-linked cleavage and polyadenylation site in HeLa cell nuclear extract is shown to occur at an early step in splicing, the binding of U2AF 65 to the pyrimidine tract of the intron 3′ splice site. The carboxyl terminus of poly(A) polymerase (PAP) previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(26 citation statements)
references
References 64 publications
(108 reference statements)
1
24
0
Order By: Relevance
“…In addition to its crucial role in splicing, we have demonstrated that U2AF 65 bound to the polypyrimidine tract of the second and last intron of β‐globin pre‐mRNA promotes 3′ end processing (Millevoi et al , 2002). We have also previously demonstrated that U2AF 65 interacts with PAP (Vagner et al , 2000). Through this interaction, PAP is able to recruit U2AF 65 to an adjacent upstream 3′ splice site, thereby stimulating splicing (Vagner et al , 2000).…”
Section: Introductionmentioning
confidence: 66%
“…In addition to its crucial role in splicing, we have demonstrated that U2AF 65 bound to the polypyrimidine tract of the second and last intron of β‐globin pre‐mRNA promotes 3′ end processing (Millevoi et al , 2002). We have also previously demonstrated that U2AF 65 interacts with PAP (Vagner et al , 2000). Through this interaction, PAP is able to recruit U2AF 65 to an adjacent upstream 3′ splice site, thereby stimulating splicing (Vagner et al , 2000).…”
Section: Introductionmentioning
confidence: 66%
“…RNase protection assays demonstrated that the UTE assists recognition of the weak cleavage-polyadenylation site, thereby coupling splicing with cleavage and polyadenylation. Interactions of splicing factors with cleavage and polyadenylation factors have been described, for example between U2AF65 and the carboxy terminal region of the poly(A) polymerase (Vagner et al 2000), cleavage and polyadenylation specificity factor (CPSF) (Kyburz et al 2006), or cleavage factor I CF1(m) (Millevoi et al 2006). The UTE is in close vicinity to the branch point, which binds the U2 snRNP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mutation of the 3′SS causes a transcription termination defect due to failure to recognize the poly(A) site (Dye & Proudfoot, 1999 ). Interactions between splicing factors, such as SF3B1 or U2AF65, and CPA factors, such as CPSF100 or poly(A) polymerase, PAPOLA, have been demonstrated (Niwa et al , 1990 ; Gunderson et al , 1994 ; Vagner et al , 2000 ; Kyburz et al , 2006 ; Tellier et al , 2020a ). In addition, subunit CDC73 of the PAF complex, which plays a role in elongation, interacts with the CPSF73 CPA endonuclease (Rozenblatt‐Rosen et al , 2009 ).…”
Section: Introductionmentioning
confidence: 99%